Improvement of internal audit in budgetary organizations - Kodirov Shukhratbek Kutbidinovich; Khojiboev Mukhiddin Shodimukhammedovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Carrying out audit and control works in the conditions of the market economy will improve the management of our entire economy, introduce economic management into the activities of trade organizations, accountancy and take a new approach to auditing. For this, further emphasis should be placed on the training of economists, including auditors. In the conditions of market relations, at the same time with state enterprises, Joint-Stock Companies, companies, rent, small enterprises and joint-ventures operate in our economy. These enterprises carry out their activities in accordance with the laws "on property", "on enterprises", "on entrepreneurship" and other normative documents adopted in our republic.